2013
DOI: 10.1021/la304122f
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Three-Dimensional Chiral Nanostructures Based on Stepwise Glancing Angle Deposition Technology

Abstract: The chiral structures have displayed some inevitable and fascinating properties in many research fields, such as chemistry, biology, mathematics, and physics. In this Article, we report the use of stepwise glancing angle deposition technology to produce the 3D chiral nanostructures. Through the optimization of deposition parameters (such as the orientation angle of poly styrene spheres (PSs) array, the deposition angle, thickness, and number), a great number of chiral structures have been achieved, and their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref. Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 45%
See 2 more Smart Citations
“…Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref. Such ultrabroadband chiral resonance in the visible region has been rarely seen in previous studies and the measured CD strength is far more stronger than those reported previously for 3D helically stacked PCMs prepared by a similar GLAD method [3,36,37,40,41] (CD of ≈0.1 in ref.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 45%
“…[40] and ≈0.04° at normal incidence in ref. [36,37]. More importantly, we would like to point out that such an ultrabroadband superchiral response observed in our SPPCMs is originated from the formation of definite handedness in all microscale domains in the same sample and therefore it eliminates the problem of random local chiralities reported in refs.…”
Section: Superposition Of Local Chiralitiesmentioning
confidence: 53%
See 1 more Smart Citation
“…With the help of various masks, such random nanohole array [26], square nanoparticle array [27], and aligned ZnO nanorods [28], various CPS with chiroptical resonance located in the near-infrared and visible region have been achieved. Particularly, our previous work also demonstrates that with the help of assembled polystyrene (PS) sphere array, a kind of shell-like chiral nanostructures can be achieved [29]. This kind of CPS can combine the magnetic or dielectric spheres to form chiral “Janus particles” [30] or “patchy particles” [31, 32] and will find potential applications in the colloid field.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of these assemblies are based on patchy colloidal particles with symmetric patches (in most cases circular patches). Recent interest in asymmetric patches has been caused by the prediction and observation of the chiroptical effect for such patches, 15 which provides new applications for particles with patches of asymmetric shapes.…”
Section: ■ Introductionmentioning
confidence: 99%